The Influence of Capital Structure, Bank Size on Profitability: Comparative Evidence from KSA and UAE Banks - Sharma, Raj Bahadur (International Review of Management and Marketing, 2026)
In essence, the financial performance of the banking sector is an important, overarching indicator of a bank's ability to meet the expectations of key stakeholders, including regulators, depositors, and shareholders, while ensuring financial stability and supporting sustainable long-term growth. This paper investigates the influence of bank size, leverage, and Tier 1 capital on the profitability of banks operating in the KSA and UAE over the period 2015–2024. The measurement variables for profitability are specified as ROA, ROE, and EPS, whereas explanatory variables are leverage ratios, TDTA, Tier 1 capital ratios, and size of the banks. Examining the results from multiple regression analysis, it can be evaluated that size has a significant effect in accounting for the determinants in the measurements of profitability in both systems. Additionally, it has been indicated in the results that in banks located in KSA, TDTA has a significant adverse effect in accounting for the measurements of profitability in KSA banks in comparison to other variables, i.e., an increase in debt has a direct adverse effect on returns generated for shareholders. However, in terms of UAE banks, the results indicates that the size has a significant effect in accounting for the measurements of profitability as represented by the model in comparison to other variables, whereas Tier 1 capital has a limited effect. In conclude, these findings highlight the significance of scale within banking organizations to drive profitability improvements. Moreover, these findings suggest that leverage and capital structure have varying significance with respect to KSA and UAE banks. Finally, this study found that based on comparative analysis, size is considered to have a significant influence on profitability with respect to KSA and UAE banks. In contrast, leverage and debt indicate varying and limited impacts, particularly with respect to UAE banks.